Influence Factors of Shear Capacity of UHPC-CA Beams Reinforced by High Strength Bars - TANG Jiajun; GUO Can; PEI Changchun; WANG Tan; LI Jiuyang (Renmin Zhujiang)
This paper analyzes the influence of seven factors,namely shear span ratio,stirrup grade,stirrup diameter,stirrup spacing,section width,section height and concrete grade,on the shear capacity of beams made of ultra high performance concrete with coarse aggregate (UHPC-CA) and reinforced by high strength bars by orthogonal test.The results show that:The influence of various factors on the shear capacity of UHPC-CA beams reinforced by high strength bars is in the order of concrete grade>section width>section height>shear span ratio>stirrup diameter>stirrup spacing>stirrup grade.The shear capacity of UHPC-CA beams reinforced by high strength bars decreases with the increase of shear span ratio and stirrup spacing,and improves with the increase of stirrup grade,stirrup diameter,section width,section height and concrete grade.